2020
DOI: 10.1155/2020/3173281
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants: A Review of Studies on Human and Animal Coronavirus

Abstract: The outbreaks of viruses with wide spread and mortality in the world population have motivated the research for new therapeutic approaches. There are several viruses that cause a biochemical imbalance in the infected cell resulting in oxidative stress. These effects may be associated with the development of pathologies and worsening of symptoms. Therefore, this review is aimed at discussing natural compounds with both antioxidant and antiviral activities, specifically against coronavirus infection, in an attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 117 publications
(131 reference statements)
0
43
0
Order By: Relevance
“…Several viruses including coronavirus that cause a biochemical imbalance in the infected cell resulting in oxidative stress, which may be associated with the development of pathologies and worsening of symptoms 30,31 . Thus, the lower SOD level may indicate a worse prognosis, and antioxidants should be considered as a candidate therapeutic approach against SARS‐CoV‐2 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Several viruses including coronavirus that cause a biochemical imbalance in the infected cell resulting in oxidative stress, which may be associated with the development of pathologies and worsening of symptoms 30,31 . Thus, the lower SOD level may indicate a worse prognosis, and antioxidants should be considered as a candidate therapeutic approach against SARS‐CoV‐2 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lipoic acid was shown to protect against RNA virus-induced gliotoxicity [ 278 ] and inhibit viral replication of HIV [ 279 ]. Further, a recent review by Diniz et al [ 280 ], highlights the possible adjunctive properties of natural antioxidants, especially flavonoids, for conventional antiviral therapies. In this report, the authors identify specific corona virus proteins that are targeted by these natural antioxidants to contribute towards the observed antiviral properties.…”
Section: Adjunctive Psychotropic Treatments During Sars-cov-2 Infectimentioning
confidence: 99%
“…Moreover, clinical data have suggested that AKI represents poor prognosis and is associated with high mortality of patients with SARS-CoV-2 in ICU settings, especially in those with underlying comorbidities and requiring renal replacement therapy [3,9]. For example, a study that analyzed the clinical characteristics and complications in fatal cases with coronavirus disease 2019 (COVID- 19) in Renmin Hospital of Wuhan University in China reported that 14 patients suffered from renal injury after the infection of SARS-CoV-2 in 92 deceased patients with COVID-19. AKI was determined based on levels of SCr, BUN, and GFR found in these 14 patients and compared with the cases without renal injury.…”
Section: Coronavirus and Acute Kidney Injurymentioning
confidence: 99%
“…Quercetin is a widespread flavonoid found in a large variety of medicinal plants and dietary supplements present in oriental and occidental diets, such as green teas, oranges, lettuces, potatoes, onions, and tomatoes [17,18]. Furthermore, it has inhibitory activity against severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) [19]. Numerous studies have shown the nephroprotective effects of quercetin against obstructive, oxidative, and inflammatory renal damage in a large spectrum of experimental models of AKI [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation